2015
DOI: 10.1007/s10339-015-0702-0
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of reality and fiction in art perception: pictorial space, body sway and mental imagery

Abstract: BackgroundThe thesis of embodied cognition claims that perception of the environment entails a complex set of multisensory processes which forms a basis for the agent’s potential and immediate actions. However, in the case of artworks, an agent becomes an observer and action turns into a reaction. This raises questions about the presence of embodied or situated cognition involved in art reception.AimsThe study aimed to assess the bodily correlates of perceiving fictional pictorial spaces in the absence of a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Research practice is mixed on this issue, even in the lab setting where counterbalancing procedures is generally not problematic. Some studies measured individual differences before other visuo-cognitive measures were taken (e.g., McCaffery et al, 2018, in face matching task; Muhl-Richardson et al, 2018, in visual search task; Sarsam et al, 2021, in scene perception task; Colver & El-Alayli, 2016, Trawiński, Mestry, et al, 2021, in art appreciation task), others took visuo-cognitive before individual difference measures (Peltier & Becker, 2017, in visual search task; Ganczarek et al, 2015; Risko et al, 2012; Sherman et al, 2015), while some counterbalanced tasks (e.g., Megreya & Bindemann, 2013, in face identification task). Moreover, we could not find clear evidence that task order influences visual exploration, with the exception of one study for which subsequent analyses did not find evidence of such an effect (Trawiński, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research practice is mixed on this issue, even in the lab setting where counterbalancing procedures is generally not problematic. Some studies measured individual differences before other visuo-cognitive measures were taken (e.g., McCaffery et al, 2018, in face matching task; Muhl-Richardson et al, 2018, in visual search task; Sarsam et al, 2021, in scene perception task; Colver & El-Alayli, 2016, Trawiński, Mestry, et al, 2021, in art appreciation task), others took visuo-cognitive before individual difference measures (Peltier & Becker, 2017, in visual search task; Ganczarek et al, 2015; Risko et al, 2012; Sherman et al, 2015), while some counterbalanced tasks (e.g., Megreya & Bindemann, 2013, in face identification task). Moreover, we could not find clear evidence that task order influences visual exploration, with the exception of one study for which subsequent analyses did not find evidence of such an effect (Trawiński, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An artwork gives rise to movement, both in terms of actual bodily movements and embodied perceptions of movement in the viewer (van Klaveren, Ueding, & Cox, 2019), also known as the emotionally-driven "being moved" (Pelowski, Markey, Forster, Gerger & Leder, 2017). Some studies have reported how artworks are able to elicit distinct movement patterns in a viewer, such as body sway and eye movements (Ganczarek, Ruggieri, Nardi & Belardinelli, 2015;Kapoula et al, 2011Kapoula & Gaertner, 2015;Taylor, Spehar, Van Donkelaar & Hagerhall, 2011), both of which are subtle indicators of people's attunement to the environment. Nevertheless, people's actual bodily movements while viewing art have hardly been a topic of systematically empirical investigation.…”
Section: Embodied Art Experiencementioning
confidence: 99%
“…posturography) of participants looking at abstract paintings. As part of postural control, both leaning posture (Chisholm, Risko & Kingstone, 2013) and postural sway (Pellecchia, 2003;Ramenzoni, Riley, Shockley & Chiu, 2007) have proven to be reflective of people's cognitive and attentional states and their perceptual attunement to the environment, including those during aesthetic experiences (Ganczarek et al, 2015;Kapoula et al, 2011Kapoula & Gaertner, 2015). Postural sway refers to the subtle, continuous and involuntary movements around the body's center of gravity which one makes while standing, so as to maintain balance and attune to the environment.…”
Section: The Present Studymentioning
confidence: 99%
“…"process of information pickup that involves the exploratory activity of looking around, getting around" (p. 147 (Brinck, 2018). Studies have shown connections between looking/visual aspects and distinct body movements such as posture/leaning into paintings with pictorial depth (Kapoula et al, 2011;Ganczarek et al, 2015) fixation/saccade duration may relate to movement and perception stage (orienting, focus on details, etc. ); e.g., mean fixation durations for abstract artworks increases as viewing time progresses (Heidenreich & Turano, 2011) • Relationship between looking and art experience: Focus of gaze, especially when considering embodied agents, may show relation to appraisal, cognition, emotion:…”
Section: Notable Theoretical and Empirical Suggestionsmentioning
confidence: 99%